Penyerapan kosakata Melayu dan Jawa pada bahasa Sunda di Banten - Rahmansyah, Sutiadi; Ardiansyah, Tesa (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2020)
Sundanese is the mother tongue of most residents in the West Java province and the Banten province of Indonesia. Sundanese is present as a language of communication in the society, a language of instruction in elementary schools, a language in published literature and news, as well as a language in traditional ceremonies. This article discusses the borrowing of Malay and Javanese vocabulary in Sundanese that is spoken in Banten province. Data were collected in the Kencana Harapan Village, located in Lebak Wangi District, parts of the Serang Regency, Banten. A descriptive qualitative method, comprising of note taking technique and an observation method, was used in this study. In addition, an interview was conducted to improve the data. The results showed that Malay and Javanese borrowings are present in Sundanese spoken in the research area. Vocabulary categories of Malay and Javanese found were not only limited to nouns but also other categories such as verbs, adjectives and numerals. The process may take place due to geographical, social, and political factors.